2011
DOI: 10.1128/mcb.00989-10
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Levels of the Hydroxmethylglutaryl-Coenzyme A Reductase Inhibitor Lovastatin Activate Ras Signaling via Phospholipase D2

Abstract: Hydroxmethylglutaryl (HMG)-coenzyme A (CoA) reductase inhibitors (statins) lower serum cholesterol but exhibit pleiotropic biological effects that are difficult to ascribe solely to cholesterol depletion. Here, we investigated the effect of lovastatin on protein prenylation and cell signaling. We show that high concentrations (50 M) of lovastatin inhibit Ras, Rho, and Rap prenylation but that therapeutic levels of lovastatin (50 nM to 500 nM) do not. In contrast, depletion of cellular cholesterol by therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…It has been demonstrated that radiation therapy can increase inflammation during therapy [45,46], but it is not clear if these effects may lead to increased risk of recurrence. Future research needs to be done on the mechanistic effects of statins as anticancer agents; however, studies should be performed using concentrations more likely to be seen in vivo to give them a more sound basis [15,17]. Perhaps, another research angle would be to discover a way to deliver in vitro concentrations of statins to the cancer site safely and effectively [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that radiation therapy can increase inflammation during therapy [45,46], but it is not clear if these effects may lead to increased risk of recurrence. Future research needs to be done on the mechanistic effects of statins as anticancer agents; however, studies should be performed using concentrations more likely to be seen in vivo to give them a more sound basis [15,17]. Perhaps, another research angle would be to discover a way to deliver in vitro concentrations of statins to the cancer site safely and effectively [47].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that a 40-or 80-mg dose of lovastatin led to a serum concentration of about 50 nM 6 h later [16]. However, most studies that demonstrate statin-mediated inhibitions in Ras protein isoprenylation use statin concentrations that are significantly higher [15]. Therefore, it remains to be seen if these promising effects in vitro will be realized in vivo.…”
Section: Pleiotropic Effectsmentioning
confidence: 93%
See 2 more Smart Citations
“…There is a report that high concentrations (50 mM) of lovastatin inhibit the Ras signaling pathway (4). These antiproliferative and pro-apoptotic properties suggest that statins could also inhibit carcinogenesis, thereby impacting cancer outcomes (5).…”
Section: Introductionmentioning
confidence: 99%